2020
DOI: 10.1515/commun-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in preferences for emotionally-meaningful versus knowledge-related appeals

Abstract: Socioemotional selectivity theory (SST), an influential life-span theory, suggests that older adults prefer persuasive messages that appeal to emotionally-meaningful goals over messages that appeal to knowledge-related goals, whereas younger adults do not show this preference. A mixed-factorial experiment was conducted to test whether older adults (≥65 years) differ from younger adults (25–45 years) in their preference for emotionally-meaningful appeals over knowledge-related appeals, when appeals are clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Conversely, knowledge of the plant did not differ by age (Table 2). These results are not consistent with those of previous studies (Chen et al, 2020;van Der Goot et al, 2021). This may be because living in a particular region for an extended period can be more important than age in terms of acquiring knowledge related to javanese edelweiss.…”
Section: Breakdown Of Conservation Awarenesscontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, knowledge of the plant did not differ by age (Table 2). These results are not consistent with those of previous studies (Chen et al, 2020;van Der Goot et al, 2021). This may be because living in a particular region for an extended period can be more important than age in terms of acquiring knowledge related to javanese edelweiss.…”
Section: Breakdown Of Conservation Awarenesscontrasting
confidence: 99%
“…Our findings suggest that men had higher knowledge about javanese edelweiss than women (Table 2). Previous studies have shown that men have higher knowledge and experience than women with regard to interaction with nature (Chen et al, 2020;Zhang et al, 2020;van Der Goot et al, 2021). The differences in the knowledge between male and female Tengger people may be due to several reasons.…”
Section: Breakdown Of Conservation Awarenessmentioning
confidence: 97%
See 1 more Smart Citation
“…Another potential explanation is that the association between exploratory processing and well-being in younger adults may be less robust than that between redemptive processing and well-being in older adults. For example, while van der Goot et al (2021) found older adults to prefer emotionally meaningful appeals over knowledge-based appeals, they found younger adults to have no preference.…”
Section: Discussionmentioning
confidence: 98%
“…For example, while van der Goot et al. (2021) found older adults to prefer emotionally meaningful appeals over knowledge‐based appeals, they found younger adults to have no preference.…”
Section: Discussionmentioning
confidence: 99%